Resilience in adults in the district Ica- Ica, in the context of COVID-19 - Chacaliaza Uribe, Carlos Richard (2022)
The objective of this study is to determine the levels of resilience in adults in the district Ica Ica, in the context of COVID-19. It also seeks to identify if there are significant differences according to age group, sex and sentimental situation. The population was made up of Ica citizens of legal age of both sexes, of which a representative sample of 383 people was obtained. The instruments used were the Resilience scale of Wagnild and Young (1993) in the adaptation of Gómez Chacaltana (2019) and a self-made socio-demographic file. It is concluded that most of the participants presented a very high level of resilience (65.27%). Likewise, significant differences were found in the level of resilience according to the age (p<0.05); however, no significant differences were found in the level of resilience according to gender (p>0.05) and sentimental status (p>0.05) of the participants.